Effect of Silver Nanoparticles With Thermoplastic Polyurethane on Postoperative Rehabilitation of Diabetic Patients With Open Fracture of Lower Extremities - Zhang, Dong; Yao, Dongchen; Ma, Ruofei; Nan, Shaokui; Lv, You; Zhu, Yue; Zhu, Shiwen (Frontiers in Surgery, 2022)
Objective: The retrospective study aims to explore the effect of silver nanoparticle with thermoplastic polyurethane (TPU/NS) on the rehabilitation of diabetic patients with open fracture of lower extremities. Methods: TPU/NS nanocomposites were prepared for postoperative treatment of diabetic patients with open fracture of lower extremities. Firstly, the cultured S. aureus and E. coli was used to test the antibacterial effect of TPU/NS dressing in vitro. After usage of TPU/NS dressing (observation group) and traditional dressing (control group), the inflammatory reaction, clinical treatment, functional rehabilitation, and adverse reactions in patients were compared. Results: TPU/NS dressing effectively inhibited the growth of bacteria with the minimum inhibitory concentration of 2 μg/mL. The usage of TPU/NS dressing reduced the inflammatory reaction accompanying by the lower positive rate of bacteria after the first dressing change. Besides, the times of dressing change, wound exudation stop time, wound healing time, hospital stay, and VAS score in the observation group were lower than those in the control group; In terms of the incidence of adverse reactions after treatment, it was lower in the observation group. Meanwhile, the functional rehabilitation and life quality of patients in observation group were better after treatment. Conclusion: TPU/NS dressing has function on promoting the postoperative recovery of patients by inhibiting the bacterial infection of the wound, thus improving limb function level and life quality. As a result, there was a tremendous potential to apply the constructed TPU/NS membrane into diabetic patients with open fracture, especially those with soft tissue injury.